Peran Ekspresi Visual Kreatif Pada Anak Dalam Pembentukan Budaya Hukum Generasi Masa Depan - R. Jossy Sutari Belgradoputra (Eastasouth Institute, 2026)
Creative visual activities for children are often positioned as supplementary activities and therefore are not fully understood as a medium of symbolic expression and personality formation. From a sociology of law perspective, this condition indicates a gap between legal norms that guarantee children’s rights to development and creative expression and the social practices that actually occur. This study aims to analyze the meaning and implementation of creative visual activities as social practices intertwined with legal norms and legal culture, as well as the relationships between parents and educators. The research adopts a sociology of law approach using a qualitative-empirical method and was conducted at Barli Art Studio Bandung. Data were collected through participant observation. Results show that art education helps develop sensitivity, responsibility, discipline, and self-awareness, emphasizing the importance of art education in supporting children's rights and a responsive legal culture.